Origin and distribution of the organic matter in the distal lobe of the Congo deep-sea fan – A Rock-Eval survey. (August 2017) - Baudin, François; Stetten, Elsa; Schnyder, Johann; Charlier, Karine; Martinez, Philippe; Dennielou, Bernard; Droz, Laurence
Abstract: The Congo River, the second largest river in the world, is a major source of organic matter for the deep Atlantic Ocean because of the connection of its estuary to the deep offshore area by a submarine canyon which feeds a vast deep-sea fan. The lobe zone of this deep-sea fan is the final receptacle of the sedimentary inputs presently channelled by the canyon and covers an area of 2500 km². The quantity and the source of organic matter preserved in recent turbiditic sediments from the distal lobe of the Congo deep-sea fan were assessed using Rock-Eval pyrolysis analyses. Six sites, located at approximately 5000 m water-depth, were investigated. The mud-rich sediments of the distal lobe contain high amounts of organic matter ( 3.5 to 4% Corg), the origin of which is a mixture of terrestrial higher-plant debris, soil organic matter and deeply oxidized phytoplanktonic material. Although the respective contribution of terrestrial and marine sources of organic matter cannot be precisely quantified using Rock-Eval analyses, the terrestrial fraction is dominant according to similar hydrogen and oxygen indices of both suspended and bedload sediments from the Congo River and that deposited in the lobe complex. The Rock-Eval signature supports the 70% to 80% of the terrestrial fraction previously estimated using C/N and δ 13 Corg data. In the background sediment, the organic matter distribution is homogeneous at different scales, from a single turbiditic event to the entire lobe, and changes in accumulation rates only have a limited effect on the quantity and quality of the preserved organic matter. Peculiar areas with chemosynthetic bivalves and/or bacterial mats, explored using ROV Victor 6000, show a Rock-Eval signature similar to background sediment. This high organic carbon content associated to high sedimentation rates (> 2 to 20 mm.yr −1 ) in the Congo distal lobe complex implies a high burial rate for organic carbon. Consequently, the Congo deep-sea fan represents an enormous sink of terrestrial organic matter when compared to other turbiditic systems over the world. Highlights: High organic carbon content (up to 5 wt%) of terrestrial origin in the lobe complex. Homogeneous distribution of organic matter in space and over time. Same geochemical characteristics in lobe complex as in channel-levee systems of the Congo deep-sea fan. Rock-Eval data match C/N and δ 13 Corg data. Lobe sediments are an important sink for terrestrial organic carbon.